Nursing student’s awareness, intention and perception towards the utilization of artificial intelligence (AI) in nursing practice - Sheraz, Sumbal; Shuaib , Nazia; Khan, Sheraz; Sultan, Amir; Shahid, Ahmad; Hussain, Hina (Journal of the Pakistan Medical Association, 2025)
The cross-sectional, analytical study was conducted in nursing institutes of Khyber-Pakhtunkhwa and Islamabad, Pakistan, from December 2023 to March 2024 to evaluate undergraduate nursing students’ awareness, intention and perception related to the integration of artificial intelligence in nursing practice. Of the 168 nursing students, awareness regarding AI was poor in 100 (59.1%) cases, intention was positive towards AI in 96 (56.9%) cases, and the perception of AI was poor in 88 (52.6%) cases. The heir intention to adopt artificial intelligence was positive. Nursing institutions should foster an environment friendly and supportive of artificial intelligence to enhanced the students’ perception. Key Words: Artificial intelligence, Nursing practice, Undergraduate education.